Recognize and Prevent Diabetes Mellitus with CERDIK at Mangunsari Health Center, Salatiga - Raswandaru, Marsela Riska; Karuhgair, Juan Christianto; Asyiqinnur, Ahmad; Khoirunnisa, Dian; Kulka, Gisteryana; Uropmabin, Tokon (Unram Journal of Community Service, 2024)
Diabetes mellitus is a chronic condition in which the body cannot produce or use insulin effectively, causing high blood sugar levels. Non-pharmacological therapy is one option to prevent and treat diabetes mellitus, for example "Diabetes Diet." Diabetes diet can be done by regulating carbohydrate intake, increasing consumption of fruits and vegetables, avoiding foods high in sugar, and maintaining an active lifestyle. The purpose of this community service is to provide health promotion related to diabetes mellitus and diabetes diet so that the community understands how to treat and prevent diabetes. The method of implementing health promotion is carried out using two techniques: 1) Delivery of material, 2) Demonstration related to diabetes diet. The results of community service showed an increase in participant knowledge about diabetes mellitus and how to treat and prevent it. Participants showed high involvement and enthusiasm during the activity. Evaluation of community service was carried out through oral questions and pre-post tests related to the health promotion material provided. Health promotion related to diabetes mellitus is very important for the community so that they can gain positive knowledge to improve their health.